Increased Alu RNA processing in Alzheimer brains is linked to gene expression changes. (1st March 2021) - Cheng, Yubo; Saville, Luke; Gollen, Babita; Veronesi, Ana Alvarez; Mohajerani, Majid; Joseph, Jeffrey T; Zovoilis, Athanasios
Abstract: Despite significant steps in our understanding of Alzheimer's disease (AD), many of the molecular processes underlying its pathogenesis remain largely unknown. Here, we focus on the role of non‐coding RNAs produced by small interspersed nuclear elements (SINEs). RNAs from SINE B2 repeats in mouse and SINE Alu repeats in humans, long regarded as "junk" DNA, control gene expression by binding RNA polymerase II and suppressing transcription. They also possess self‐cleaving activity that is accelerated through their interaction with certain proteins disabling this suppression. Here, we show that similar to mouse SINE RNAs, human Alu RNAs, are processed, and the processing rate is increased in brains of AD patients. This increased processing correlates with the activation of genes up‐regulated in AD patients, while increased intact Alu RNA levels correlate with down‐regulated gene expression in AD. In vitro assays show that processing of Alu RNAs is accelerated by HSF1. Overall, our data show that RNAs from SINE elements in the human brain show a similar pattern of deregulation during amyloid beta pathology as in mouse. SYNOPSIS: SINE Alu RNAs in the human brain, similar to their counterpart SINE B2 RNAs in mouse, show increased processing in amyloid beta pathology. Increased Alu processing further correlates with AD‐linked gene expression changes. Processing of Alu RNAs is increased in Alzheimer's disease (AD) patients compared with individuals with no cognitive impairment. Processing of Alu RNAs correlates with the activation of genes upregulated in AD patients, and in vitro induced degradation of Alu RNAs also activates these genes. Similar to SINE RNAs in mouse, processing of human Alu RNAs is accelerated by HSF1 in vitro . Abstract : SINE Alu RNAs in the human brain, similar to their counterpart SINE B2 RNAs in mouse, show increased processing in amyloid beta pathology. Increased Alu processing further correlates with AD‐linked gene expression changes.